Respuesta :
(10g³-8g²+5g-14)+(10g²+12g)=10g³+(-8g²+10g²)+(5g+12g)-14=
=10g³+2g²+17g-14
Anser: 10g³+2g²+17g-14
=10g³+2g²+17g-14
Anser: 10g³+2g²+17g-14
Answer:
Given the polynomial expression: [tex](10g^3-8g^2+5g-14)+(10g^2+12g)[/tex]
Remove the parenthesis, we get
[tex]10g^3-8g^2+5g-14+10g^2+12g[/tex]
Like terms states that those terms which have the same variable.
Combine like terms;
[tex]10g^3 +2g^2+17g-14[/tex]
Therefore, the polynomial which is equivalent to the polynomial [tex](10g^3-8g^2+5g-14)+(10g^2+12g)[/tex] is, [tex]10g^3 +2g^2+17g-14[/tex]